Particularities and management of late-onset rheumatoid arthritis - Enrique Martínez González; Liena Perdomo Roselló; Reiny Lorena Rosquete Ávila (Acta Médica del Centro)
Introduction: rheumatoid arthritis is an autoimmune disease with articular and extra-articular involvement. It is considered late-onset when it begins after age 60 and has its own distinctive characteristics. Objective: to analyze the demographic, clinical and treatment characteristics of late-onset rheumatoid arthritis. Methods: automated documentary review in the PubMed/Medline and Scielo databases (Google Scholar was used as a search engine) in the period between January and June 2023. 24 articles were selected, 75% updated. Results: there is a 1:1 relationship between sexes, with three fundamental forms of presentation of the disease. The clinical characteristics are heterogeneous, with greater involvement of large joints, more constitutional symptoms, stiffness and extra-articular manifestations mostly of a cardiorespiratory nature, as well as less seropositivity. The prognosis depends mainly on age, comorbidities, seropositivity and the type of treatment; which is worse than in younger patients. Therapeutic management has the same objectives as in early-onset disease and there is a tendency towards less intensive treatments with antirheumatic drugs. Conclusions: late-onset rheumatoid arthritis has particular characteristics that must be taken into account for accurate and early diagnosis, adequate therapeutic management and control of possible adverse effects and good adherence to treatment.